If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 11 = -1 Reorder the terms: 11 + 6y = -1 Solving 11 + 6y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 6y = -1 + -11 Combine like terms: 11 + -11 = 0 0 + 6y = -1 + -11 6y = -1 + -11 Combine like terms: -1 + -11 = -12 6y = -12 Divide each side by '6'. y = -2 Simplifying y = -2
| 66x=65x | | 12-3.5=2x | | -2(7x-2)=-32-2x | | 2(sin^2(3x))-1=0 | | 2(2x+6)=5x-9 | | Y=10-2(3-4x) | | 31-x=-8(1+5x) | | 18-x=9x | | 7n+12=25n-2 | | -2(4-5m)=-8+5m | | 7(1.08)-10= | | -3(4r-8)=-30 | | (x+9)(x+9)=44 | | (6x-4)+(7x-10)= | | 5n-8+6=-7 | | r+8.2+0.4=8.6 | | k-2=12+8k-5k | | 2(z+5)=3z+4 | | 400-3x=142 | | 4y+10x=2 | | -4x^2-144=0 | | 7+x-3=-1+2x | | 2x-8x-11=1-4x | | 7x-58=2x+4 | | 6x^4-16x^3-38x^2+128x-80=0 | | -3(3y-2x)+-2(5x-4y)= | | 2.33=k+2 | | (3x+17)=(5x+11) | | (2x+16)+(2x+16)+(x+14)+(x+14)=360 | | 15+b=192.44 | | 42n=180 | | 6n=30+18 |